2013
DOI: 10.1111/liv.12172
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the adjunctive probiotic VSL#3 on portal haemodynamics in patients with cirrhosis and large varices: a randomized trial

Abstract: Adjunctive probiotic (VSL#3) improved the response rate to propranolol therapy and was safe and well tolerated in patients with cirrhosis. Adjunctive probiotic therapy merits further study for reduction in portal pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 19 publications
2
65
1
1
Order By: Relevance
“…Probiotics are not drugs, but rather combinations of bacteria. In adjunctive therapy a beneficial effect has been observed in patients receiving propranolol and in addition VSL#3 as a probiotic therapy, with response rates to propranolol being subsequently improved [48]. On the other hand, probiotic administration alone did not show effects on portal pressure in compensated [49] and decompensated cirrhosis [50].…”
Section: Clinical Studiesmentioning
confidence: 99%
“…Probiotics are not drugs, but rather combinations of bacteria. In adjunctive therapy a beneficial effect has been observed in patients receiving propranolol and in addition VSL#3 as a probiotic therapy, with response rates to propranolol being subsequently improved [48]. On the other hand, probiotic administration alone did not show effects on portal pressure in compensated [49] and decompensated cirrhosis [50].…”
Section: Clinical Studiesmentioning
confidence: 99%
“…No relevant differences were observed in the frequency or type of adverse effects between the groups studied. In this study authors concluded that VSL#3 improved the response rate to propranolol therapy and was well tolerated by patients; however, the effects of supplemental probiotic therapy on portal pressure require further study (Gupta et al, 2013). …”
Section: Probiotics In Variceal Bleedingmentioning
confidence: 94%
“…The addition of probiotic therapy to propanolol improved its response rate on hepatic venous pressure gradient (HVPG) compared with adjunctive antibiotics. The mean decrease in HVPG was also greater in the probiotics-treated group (3.7 mmHg) than in the antibiotics-treated group (3.4 mmHg) and placebo group (2.1 mmHg) (Gupta et al, 2013).…”
Section: Probiotics In Decompensated Cirrhosismentioning
confidence: 97%
See 1 more Smart Citation
“…Another approach is to restore intestinal bacterial diversity by supplementing probiotics. While the impact of the probiotic VSL#3 alone on HVPG led to conflicting studies [102,103], a RCT observed an increase in haemodynamic response to NSBB in patients receiving adjunctive probiotics [104]. …”
Section: Inflammation and Bacterial Translocationmentioning
confidence: 99%